Pengaruh Disiplin Kerja Dan Turnover Intention Terhadap Kinerja Karyawan AN Sport Tasikmalaya - Nizar Alfi Naufal; Kusuma Agdhi Rahwana; Dudu Risana (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
This study aims to determine the effect of work discipline and turnover intention on employee performance in the Tasikmalaya AN Sport convection production section. The method used in this research is quantitative. With a research sample of 50 people as respondents of the Tasikmalaya Sport Convection Employees based on 50 known population data. The data used is primary data. Simultaneously, work discipline and turnover intention have a significant effect on employee performance. Partially the work discipline variable has a significant effect on employee performance, for the turnover intention variable it has no significant effect on employee performance.